1999
DOI: 10.1590/s0100-879x1999001200016
|View full text |Cite
|
Sign up to set email alerts
|

Natural preference of zebrafish (Danio rerio) for a dark environment

Abstract: The zebrafish (Danio rerio) has been used as a model in neuroscience but knowledge about its behavior is limited. The aim of this study was to determine the preference of this fish species for a dark or light environment. Initially we used a place preference test and in a second experiment we applied an exit latency test. A two-chamber aquarium was used for the preference test. The aquarium consisted of a black chamber and a white chamber. In the first experiment the animal was placed in the aquarium and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(122 citation statements)
references
References 10 publications
5
107
0
6
Order By: Relevance
“…And indeed, this was exactly what was found in a light dark preference task: zebrafish avoided the dark compartment and preferred a well illuminated compartment of a two compartment shuttle box (Gerlai et al, 2000). However, Serra et al (1999) showed that zebrafish prefer areas of the test environment with a dark background. The difference in the results of these two studies is not easy to explain but may be due to numerous methodological differences.…”
Section: Automation Is the Key For High Throughput Screeningsupporting
confidence: 68%
See 1 more Smart Citation
“…And indeed, this was exactly what was found in a light dark preference task: zebrafish avoided the dark compartment and preferred a well illuminated compartment of a two compartment shuttle box (Gerlai et al, 2000). However, Serra et al (1999) showed that zebrafish prefer areas of the test environment with a dark background. The difference in the results of these two studies is not easy to explain but may be due to numerous methodological differences.…”
Section: Automation Is the Key For High Throughput Screeningsupporting
confidence: 68%
“…The difference in the results of these two studies is not easy to explain but may be due to numerous methodological differences. For example, Serra et al (1999) used a dark background but the compartment was well illuminated. Whereas Gerlai et al (2000) used a dark compartment that was truly dark as it was covered on all sides and the top.…”
Section: Automation Is the Key For High Throughput Screeningmentioning
confidence: 99%
“…L/D choice behavior is similarly light-driven yet distinct in duration (observable within minutes to tens of minutes), and it has been reported in adult zebrafish (13,(21)(22)(23). After being individually introduced into a L/D choice chamber (light intensity readings of 300 and 160 Lux, respectively, on each side) (Fig.…”
Section: Resultsmentioning
confidence: 59%
“…Protocols to measure anxiety tend to assess one of two variables. The first set of protocols record the reaction of adult fish to novel environments, such as the amount of time spent at the edge of a tank [30,49], at the bottom of a novel tank [34,50] or on the dark side of a light/dark tank [28,51]. The second approach analyses locomotory patterns: freezing, long-lasting increases in basal locomotory activity [6,48,49] and tightening of a fish's shoal [52] have all been reported to be reliable measures of anxiety.…”
Section: Reviewmentioning
confidence: 99%